2018
DOI: 10.1007/s12265-018-9822-0
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Cardiac Mesenchymal Stem Cell-Derived Exosomes Promotes Repair in Ischemic Myocardium

Abstract: Our previous study demonstrated the beneficial effects of exosomes secreted by cardiac mesenchymal stem cells (C-MSC-Exo) in protecting acute ischemic myocardium from reperfusion injury. Here, we investigated the effect of exosomes from C-MSC on angiogenesis in ischemic myocardium. We intramyocardially injected C-MSC-Exo or PBS into the infarct border zone after induction of acute mouse myocardial infarction (MI). We observed that hearts treated with C-MSC-Exo exhibit improved cardiac function compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 49 publications
(60 reference statements)
2
71
0
1
Order By: Relevance
“…Recently, exosomes serve as substitutes for BMSCs in cellfree therapy, playing important roles in mediating heart repair during myocardial infarction injury. 11,43 The mechanisms of cardioprotection of BMSC-derived exosomes have not been fully elucidated, while the effects of anti-inflammation, immunoregulation, angiogenesis and the modulation of M1/M2 macrophage polarization have gradually attracted scholars' attention. 44 Macrophages are involved in heart injury and repair after MI and F I G U R E 5 The effects of L-Exo on inflammation and phenotype of rat peritoneal macrophages under LPS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exosomes serve as substitutes for BMSCs in cellfree therapy, playing important roles in mediating heart repair during myocardial infarction injury. 11,43 The mechanisms of cardioprotection of BMSC-derived exosomes have not been fully elucidated, while the effects of anti-inflammation, immunoregulation, angiogenesis and the modulation of M1/M2 macrophage polarization have gradually attracted scholars' attention. 44 Macrophages are involved in heart injury and repair after MI and F I G U R E 5 The effects of L-Exo on inflammation and phenotype of rat peritoneal macrophages under LPS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While the cardioprotective effect of CPC-EVs has been broadly reported, very little is currently known about their putative effect on cardiomyocyte renewal. Positive effects of EVs on in vitro cultured rat neonatal cardiomyocytes have been described [90], together with encouraging data showing Ki67+ cardiomyocytes in an MI mouse model injected with CPC-EVs; yet the mechanism of action underlying such effect still needs clarification [162,163].…”
Section: A Role For Cpc-derived Evsmentioning
confidence: 99%
“…Recent studies have shown that MSC-based treatment of ischemia-induced cardiac damage can be mediated through the secretion of exosomes [5][6][7][8][9]. MSC-secreted exosomes have been reported to exert an anti-apoptotic effect on CMCs both in vivo and in vitro [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%